2020
DOI: 10.1371/journal.pone.0241088
|View full text |Cite
|
Sign up to set email alerts
|

Uremic pruritus and long-term morbidities in the dialysis population

Abstract: Background Uremic pruritus (UP) is a multifactorial problem that contributes to low quality of life in dialysis patients. The long-term influences of UP on dialysis patients are still poorly understood. This study aims to elucidate the contribution of UP to long-term outcomes. Materials and method We used the Taiwan National Health Insurance Research Database to conduct this study. Patients on chronic dialysis were included and divided into UP and non-UP groups accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…Uremic pruritus is a multifactorial skin manifestation of ESRD and hemodialysis that affects the patients' living standards significantly 19 …”
Section: Discussionmentioning
confidence: 99%
“…Uremic pruritus is a multifactorial skin manifestation of ESRD and hemodialysis that affects the patients' living standards significantly 19 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies support the link between CKD-aP and cardiovascular mortality. Ting et al [ 9 ] showed a slight increase in major cardiovascular adverse events (HR 1.05) and heart failure (HR 1.08) and Weng et al [ 40 ] found that CKD-aP was a predictor for 2-year cardiovascular mortality in HD patients (HR 3.164).…”
Section: Impact Of Ckd-ap On Health-related Qol (Hrqol) and Medical Outcomesmentioning
confidence: 99%
“…Dialysis patients with itch are reported to have increased infection-related events, including sepsis and bacteraemia [ 9 ]. Sukul et al [ 8 ] found an increased risk of skin-related infections in HD patients with extreme itch (HR 1.41).…”
Section: Impact Of Ckd-ap On Health-related Qol (Hrqol) and Medical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of several observational studies has reported a prevalence of at least 50% in patients on dialysis [1]. CKD-aP is more than just an irritating itch; in fact, it has far-reaching effects and has been associated with increased morbidity and mortality and decreased quality of life [2][3][4]. CKD-aP affects patients on hemodialysis and peritoneal dialysis to a similar degree; however, a study on the topic has found that it affected patients on hemodialysis to a lesser extent [1,5].…”
Section: Introductionmentioning
confidence: 99%